The Hadith Reception by the Zā'irīn (Visitors) of the Tomb of Syekh Burhanuddīn in Minangkabau, North Sumatera - NOFRI ANDY.N; Eka Rizal (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2020)
The ziyāra (pilgrimage) is deeply embedded within the community of Muslims that highly upholds their local wisdom. This tradition constitutes the way they respect the ulamas and their struggles when introducing Islam to the local natives some centuries ago. This qualitative study focuses on groups of Muslims in Minangkabau who do the pilgrimage to the tomb of Syeikh Burhanuddin. Employing descriptive analytical approach, it reveals that they barely understand the hadiths related to the tradition. This leads them to simply follow the rules taught by the tuangku, their religious leaders. This study then concludes that it is important for Muslims in Minangkabau and beyond to know the related hadiths (and their contents) before conducting any religious traditions or rituals.